Synthesis and Biological Evaluation of Coumarinyl Sydnone Derivatives - Keshav C. Patel; Himanshu D. Patel (E-Journal of Chemistry)
A novel series of compounds containing coumarinyl sydnone derivatives from 4-methyl-7-hydroxy-8-nitro coumarin were synthesized. The formed compounds have been evaluated by physical methods (melting point, thin layer chromatography, elemental analysis) and by spectral data (IR, 1H-NMR & 13C NMR). The antimicrobial evaluation of the compounds showed that some of them revealed promising antimicrobial activity.